Nocturnal Frontal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The electroclinical pattern of 33 patients with familial, autosomal dominant, nocturnal frontal lobe epilepsy was studied, including video-polysomnographic monitoring in 12, at the University of Milano, School of Medicine, Italy.